Faktor-Faktor Yang Mempengaruhi Minat Investor Dalam Menggunakan Sistem Perdagangan Saham Online - Vidayana Vidayana (Journal of Business Strategy and Execution, 2012)
This study was conducted to examine the relationship between several variables that has been believed could influencing the intention to use online stock trading system on the Indonesia Stock Exchange. The model used was developed by Model TAM, TPB and ECM. Variable Satisfaction, easy to use, usfulness, trust, risk and benefits, which analyzed its association with the intention to use by using path analysis. Data taken from 62 respondents who are investors in the Indonesia Stock Exchange trade transactions online. Results from the study were analyzed using confirmatory factor analysis and path analysis showed that the variables of trust and proven usefulness secarang direct effect on the intention to use online stock trading system.